An Island Getting Divided at the Cinema: Transformational Microhistory of Cinemagoing and Nationalism in Cyprus - Bogac, Barcin (Routledge Journals, Taylor & Francis Ltd, 2023)
This study offers an alternative perspective for examining the rise of Turkish nationalism in the Eastern Mediterranean in relation to cinema culture within the political and historical contexts of Cyprus. The cinema business and its practices had their golden age in the 1950s through the distribution of Turkish films from Turkey and the increasing number of movie theatres in Turkish Cypriot neighbourhoods. This period was also crucial in terms of political developments on the island due to the drastic rise in ethnic and national divisions. Drawing on archival research and oral history; this article aims to examine how Turkish nationalism was provided with the ideal conditions to grow rapidly at Cypriot cinemas and how multi-communal cinemagoing experiences of the early 1950s had transformed into nationally divided Cypriot audiences during the last years of British colonial rule in Cyprus.
Keywords: Conflict; Film